<u>Answer</u>
y⁻¹ = ∛(4x+8)
<u>Explanation</u>
y=(1/4)x³ - 2.
To find the inverse of this equation, you first make x the subject of the formular.
y=(1/4)x³ - 2
Multiply both sides by 4;
4y = x³ - 8
Add 8 on both sides of the equation;
4y + 8 = x³
x³ = 4y + 8
Apply the cube root on both sides to get the value of x;
x = ∛(4y+8)
The inverse of y=(1/4)x³ - 2 is;
y⁻¹ = ∛(4x+8)
Answer:
distributive property
Step-by-step explanation:
they distribute the 1 to the 3 and 7 to make it easier
hope this helps
Answer:
(7,6)
Step-by-step explanation:
I believe the correct number is 88.
Answer:
8x + 3
Step-by-step explanation:
In the expression -3x + 14 - 11 + 11x, we have two pairs of like terms that can be combined together:
-3x, 11x
14, -11
If we rewrite this expression with the like terms together, it would look like this:
-3x+11x + 14-11
To make the addition of -3x and 11x easier, we could switch their places in the expression to make it look like this:
11x-3x + 14-11
(Note: Even though we are switching the terms' places, the -3x still keeps its negative sign when you move it around.
11x-3x is 8x and 14-11 is 3.
Therefore, the expression -3x + 14 - 11 + 11x can be simplified by combining like terms into 8x + 3.